Rehabilitation of speech disorders following glossectomy, based on ultrasound visual illustration and feedback. (1st September 2020) - Girod-Roux, Marion; Hueber, Thomas; Fabre, Diandra; Gerber, Silvain; Canault, Mélanie; Bedoin, Nathalie; Acher, Audrey; Béziaud, Nicolas; Truy, Eric; Badin, Pierre
ABSTRACT: Intraoral surgery for tongue cancer usually induces speech disorders that have a negative impact on communication and quality of life. Studies have documented the benefit of tongue ultrasound imaging as a visual articulatory feedback for speech rehabilitation. This study aims to assess specifically the complementary contribution of visual feedback to visual illustration (i.e. the display of ultrasound video of target language movements) for the speech rehabilitation of glossectomised patients. Two therapy conditions were used alternately for ten glossectomised French patients randomly divided into two cohorts. The IF cohort benefitted from 10 sessions using illustration alone (IL condition) followed by 10 sessions using illustration supplemented by visual feedback (IL+F condition). The FI cohort followed the opposite protocol, i.e. the first 10 sessions with the IL+F condition, followed by 10 sessions with the IL condition. Phonetic accuracy (Percent Consonants Correct) was monitored at baseline (T0, before the first series) and after each series (T1 and T2) using clinical speech-language assessments. None of the contrasts computed between the two conditions, using logistic regression with random effects models, were found to be statistically significant for the group analysis of assessment scores. Results were significant for a few individuals, with balanced advantages in both conditions. In conclusion, the use of articulatory visual feedback does not seem to bring a decisive advantage over the use of visual illustration, though speech therapists and patients reported that ultrasound feedback was useful at the beginning. This result should be confirmed by similar studies involving other types of speech disorders.